2013
DOI: 10.1037/a0033217
|View full text |Cite
|
Sign up to set email alerts
|

Universal Design for Learning and elementary school science: Exploring the efficacy, use, and perceptions of a web-based science notebook.

Abstract: Science notebooks can play a critical role in activity-based science learning, but the tasks of recording, organizing, analyzing, and interpreting data create barriers that impede science learning for many students. This study (a) assessed in a randomized controlled trial the potential for a web-based science notebook designed using the Universal Design for Learning (UDL) framework to overcome the challenges inherent in traditional science notebooks, (b) explored how teacher characteristics and student use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 61 publications
1
58
0
1
Order By: Relevance
“…In particular, those learners who would most benefit from such supports are least likely to access those features (Karabenick & Newman, ; Roll, Aleven, McLaren & Koedinger, ). However, guidance and feedback about using supports can improve help seeking (Rappolt‐Schlichtmann et al , ; Roll et al , ); the ongoing question remains how to approach such guidance and feedback in a way that translates to enduring self‐understanding and metacognitive skills for students, particularly outside of highly controlled online environments.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, those learners who would most benefit from such supports are least likely to access those features (Karabenick & Newman, ; Roll, Aleven, McLaren & Koedinger, ). However, guidance and feedback about using supports can improve help seeking (Rappolt‐Schlichtmann et al , ; Roll et al , ); the ongoing question remains how to approach such guidance and feedback in a way that translates to enduring self‐understanding and metacognitive skills for students, particularly outside of highly controlled online environments.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have examined how UDL can be applied to teacher-developed lessons and curricula (Browder, Mims, Spooner, Ahlgrim-Delzell, & Lee, 2008;Dymond et al, 2006;King-Sears et al, 2015). Several studies have examined academic outcomes and engagement with UDL-based digital learning environments (Coyne, Pisha, Dalton, Zeph, & Smith, 2012;Dalton, Proctor, Uccelli, Mo, & Snow, 2011;Hall, Cohen, Vue, & Ganley, 2015;Marino et al, 2014;Rappolt-Schlichtmann et al, 2013). Studies have demonstrated that UDL-based instruction results in positive academic gains and increased engagement for students.…”
Section: Background On Udlmentioning
confidence: 99%
“…The UDL broadens the understanding of the processes by which students access knowledge, not only by taking into consideration resources that eliminate barriers, but also by developing and designing appropriate courses and curricula, and for that reason, it is not possible to speak of curricular adaptation. This is one of its premises: barriers to learning occur at the intersection with the curriculum (RappoltSchlichtmann, Daley, Robinson, & Johnson, 2013). The UDL has proven itself as a great ally to design instruction in courses, materials and content in order to benefit people of all learning styles without adaptation or replacement of equipment (Zhong, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties for applicability of the UDL draw attention to possible situations to be located in our research contexts and practices, such as: extra time used by the teacher for improvement and preparation of material (Rao & Tanners, 2011;Katz, 2015); limited/insufficient teacher education in the theme of UDL (Frey, Andres, Mckeeman, & Lane, 2011;Smith, 2012;Caruana et al, 2015); few computers in schools and limited access to the internet (Rappolt-Schlichtmann et al, 2013;Katz, 2015;KingSears et al, 2015); and poorly inclusive public policies (Katz, 2015). These situations, located in studies of different realities that are similar to local issues, are not a reason to diminish the research development and practical application of the UDL, since there is an understanding that…”
Section: Universal Design For Learningmentioning
confidence: 99%
See 1 more Smart Citation